Key factors affecting strategy-minded decision makers in their innovations choices - Barbosa, Fernando (2013)
The rapid and continuous pace of technological change is a major challenge for all managers, who are often faced with innovations’ adoption decisions affecting the future of their companies. This is a fundamental issue on strategy, if we see strategy as a set of actions to make critical choices between two or more alternatives, in order to achieve competitive advantages or to respond to competitors. Strategy‐minded leaders try to predict the value that they will create with their choices in the organization. However, formulating strategy is a difficult task, due to the high level of uncertainty hampering the anticipation of future trends. An even harder work is the implementation of strategy, due to its interdependent relationship with strategy formulation, which is materialized in the organizational structure dedicated to fulfil the organization goals. In this work we propose to look at the factors that strategy‐minded leaders perceive that influence the adoption of innovations and we explore their relationships within several academic fields, of study, namely strategic management, organization theory, organization behaviour and organization development, adopting an holistic perspective that will allow for a better understanding of strategic adoption decisions. This analysis is grounded on field work that involved the collection of primary data from different enterprises. The research was based on a quantitative approach and on an intentional non‐probabilistic sampling strategy. The sample includes thirty four Portuguese firms, from different sectors. The selection criteria was based on the innovative performance of the firm, and on the concomitant presumption that innovative activities are well structured inside the firm. The sample includes micro, small, medium and large firms. A proportion of the sample includes conglomerates, and in fact, the sample represents approximately one hundred and twenty two firms, and a significant proportion of Portuguese gross expenditure on business R&D. A quantitative structured questionnaire was the main instrument of data collection, but some interviews with selected firms were also realized, in order to substantiate or consolidate some of the data that was obtained through the questionnaire. In this paper we present the preliminary results of the analysis of that data. Investment scheduling and costs appraisal, quantitative and qualitative advantages of the technology and strategic implications of its adoption are the factors that most often influence the decision of innovation adoption and the less common factors include the degree of formalization of decision procedures and the level/extent of the hierarchical chain.